Surveillance of pesticide poisoning in colombia (2000)
The objective of this article is to realize a critical review of the epidemiologic surveillance of pesticide-related health effects in Colombia. First, it describes the historic changes in the exposure to pesticides in the country, the expected and potential adverse health effects (chronic, acute, and subacute). Second, it reviews some epidemiologic surveillance systems actually used in Colombia with their strongholds and weakness. Finally, it proposes some basic issues to improve this important public health activity.